2017
DOI: 10.4236/jtts.2017.71006
|View full text |Cite
|
Sign up to set email alerts
|

Study on Geometric Factors Influencing Saturation Flow Rate at Signalized Intersections under Heterogeneous Traffic Conditions

Abstract: The main objective of intersection design is to facilitate the convenience, comfort, and safety of people traversing the intersection by enhancing the efficient movement of road users. The intersections on urban roads in India generally cater to heterogeneous motorized traffic, along with slow-moving traffic including pedestrians. It is therefore necessary to consider saturation flow for mixed traffic conditions to evaluate the overall operation of signalized intersections. A proper traffic model must consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…However, it was found that the turning radius significantly affects the value of SFR with a p-value equal to 0.000 for the LUTM-SFR model. These results are consistent with other research outcomes [7,14,15].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, it was found that the turning radius significantly affects the value of SFR with a p-value equal to 0.000 for the LUTM-SFR model. These results are consistent with other research outcomes [7,14,15].…”
Section: Resultssupporting
confidence: 93%
“…In India, several studies investigated the factors affecting SFR. It was found that the turning radius and gradient [14,15], the proportion of turning vehicles [14][15][16], right-turning movements [17,18], road width and the number of lanes [17][18][19], and the percentage of heavy vehicles [18] had a significant effect on the estimation of SFR.…”
Section: Introductionmentioning
confidence: 99%
“…When examining traffic flow on a specific section of the road, several overarching factors come into play. These include the overall road infrastructure both within and outside the section being studied [88][89][90], as well as temporary factors that can be cyclic, like changes in time of day and seasons [35,91,92], or random, such as variations in weather conditions [93].…”
Section: Analysis Of the Influence Of The Dynamics Of The Pts On The ...mentioning
confidence: 99%
“…This discrepancy is due to the behavior difference between evacuees and motor vehicles. Evacuees are more mobile than motor vehicles, and can ignore the lane limit, turning radius, traffic signals and other control measures for motor vehicles [19,60,61]. Furthermore, due to the difference in volume size between people and motor vehicles, evacuees have relatively sufficient space at the urban level and can choose evacuation routes more freely.…”
Section: Parametric and Synergistic Effect Analysismentioning
confidence: 99%